Invasion by the chestnut gall wasp in Italy causes significant yield loss in Castanea sativa nut production. (16th December 2013) - Battisti, Andrea; Benvegnù, Isadora; Colombari, Fernanda; Haack, Robert A.
Abstract The Asian chestnut gall wasp Dryocosmus kuriphilus Yasumatsu (Hymenoptera Cynipidae) is an invasive species in chestnut forests and orchards in many parts of the world. Nuts produced by the European chestnut (Castanea sativa Miller) are important in human food and culture, and as a component in food webs in forest ecosystems. Severe infestations are reported to reduce nut yield, although precise data are lacking because of large natural year‐to‐year variability in yield. The recent colonization of chestnut orchards in north‐eastern Italy, where nut yield has been continuously and precisely recorded for several years, offered an opportunity to calculate the impact of gall wasp infestation level on yield. The nut yield of C. sativa chestnut trees was negatively related to the gall wasp infestation level, with losses as high as 80% being reported when the number of current‐year galls was above six galls per 50‐cm twig. Yield losses can be explained by direct and indirect factors related to gall formation, and a fuller understanding of the mechanisms involved could identify possible mitigation measures.